The Oxford book of Latin American short stories - González Echevarría, Roberto (New York : Oxford University Press, 1999)
"Includes 53 stories spanning evolution of short fiction in Brazil as well as Hispanic America across a broad range of writing from colonial era and 19th century to modern favorites such as Lugones, Quiroga, Lima Barreto, Borges, Cortázar, Rulfo, Ribeyro, Castellanos, Lispector, Ferré, and Monterroso, in versions by distinguished translators. An essay by the editor traces evolution of the genre. Brief headnotes for each period and author and a short bibliography provide ample contextualization. Recommended for classroom use"--Handbook of Latin American Studies, v. 58.
Includes bibligraphical references (p. 473-475) and index..
Keywords: Short stories, Latin American -- Translations into English